The fabrication of novel microfluidic devices for chemical separation and concentration enrichment of amino acids, proteins, peptides, particles, and cells - Roman, Gregory T. (Kansas State University, 2006)
My doctoral dissertation consists of three fundamental studies: 1) synthesis of biocompatible materials that can be used as microfluidic substrates, 2) characterizing these materials with respect to properties important to microfluidic fabrication, biochemical separations and concentration enrichment, and 3) employing these novel devices for real world applications in bioanalytical chemistry. The surface properties of a substrate will dramatically affect the resolution and efficiency that can be obtained for a specific CE separation. Thus, the ability to modify the surface is very useful in tailoring a microfluidic chip to a specific separation mode. The substrates we have synthesized for microfluidic devices include metal oxide modified poly(dimethylsiloxane) (PDMS), poly(ethyleneoxide)-PDMS (PEO-PDMS) coblock polymers, and surfactant coated PDMS. The metal oxide modified PDMS materials we synthesized include silica-PDMS, titania-PDMS, vanadia-PDMS and zirconia-PDMS. The surfaces of these materials were characterized using contact angle, X-ray photoelectron spectroscopy (XPS), Raman, transmission electron microscopy (TEM), scanning electron microscopy (SEM), atomic force microscopy (AFM) and electroosmotic mobility (EOM) measurements. All of the metal oxide modified PDMS surfaces were significantly more hydrophilic than native PDMS, suggesting potential application in separations of biopolymers. In addition to being more hydrophilic the EOF and zeta potential of the channels were stable and quite durable with aging. Well characterized silane chemistry was used to derivitize the surface of the PDMS metal oxide surfaces allowing a number of different functionalities to be placed on the surface. This method has the potential for wide applicability in many different fields, but specifically for the fabrication of microstructures that need specific surface chemistries. We have also made a number of advancements using sol-gel chemistry and laminar flow within microfluidic channels to fabricate nanoporous membranes. Sol-gel patterned membranes are a simple and facile method of incorporating nanoscale diameter channels within a microfluidic manifold. These membranes have been used to perform preconcentration of amino acids, proteins and small particles for further analysis and separation using CE. We are also using these membranes for further study in desilanization and protein recrystallization studies.
Keywords: microfluidic; sol-gel; Chemistry, Analytical (0486)